Economic Growth Improvement Strategies with Infrastructure Investment Approach in Situbondo District - Farizkha, Ivan Agusta Farizkha (Aspirasi Masyarakat Intelektual Islam Nusantara, 2022)
In an effort to boost a region's economic growth, infrastructure development is a highly significant aspect. This study aims to explain the relationship between the development of road infrastructure and regional economic growth in Situbondo Regency. It is anticipated that highly connected metrics would be utilized to evaluate national and regional initiatives. Furthermore, it may demonstrate the impact of investment in public works infrastructure, particularly infrastructure, on the success of economic sector development and provide strategic suggestions to boost economic growth. This research use the approach of Correlation and Regression Test Analysis in order to examine the close relationship between two or more variables. In the meanwhile, the secondary data utilized includes information on five indicators of public works infrastructure. Following are the Gross Regional Domestic Product (GRDP) statistics and its nine components as income-based indices of economic progress. Indicators of GRDP economic development and indicators of public works infrastructure, such as roads, bridges, and irrigation, are correlated, according to the findings of the correlation test conducted from 2014 to 2018.